Do We Deliver What They Expect? Finding the Gap Between Users' Expected and Currently Received Library Services. - Ara, Mehvish; Soroya, Saira Hanif (Pakistan Library & Information Science Journal, 2018)
This research aims to assess tire service quality of public libraries of Lahore by evaluating the disparities between the users' expectation and currently received services. The survey method based on questionnaire was used. Four of the largest libraries in Lahore, in terms of services, collection and other facilities, were the population of the study. A sample of four hundred library users was selected with one hundred library users for each library based on convenience sampling. A modified LibQUAL+ tool was adopted to collect the data. The findings revealed that users have very high expectations regarding the accessibility of library's electronic resources from home or office, library website, printed material, availability of electronic information resource, modem equipment, tools that allow the users to find the material themselves, and provision of the information in an easy manner. The findings are helpful for public libraries' authorities to redcsign/upgradc the quality of library services, policies and procedures according to users' expectations and requirements.
Keywords: ACCESS control; INTERNET access for library users; LAHORE (Pakistan); LIBRARY public services; LIBRARY records; Libraries; Libraries and Archives; PUBLIC libraries; dept.ils